Half yard gifts : easy sewing projects using left-over pieces of fabric - Shore, Debbie (Writer on sewing) (Search Press, 2016)
Contains 22 projects to sew and give away, each made using less than half a yard of fabric. The book contains gifts for all your family and friends: the projects range from pincushions, bags and paperweights to aprons for budding chefs, kneeling pads for gardeners and tool belts for DIY-enthusiasts. The projects are made in a range of prints and styles and use a range of techniques: either follow each project closely, or adapt the size and fabric to suit the recipient. Debbie gives advice on how to customise the projects, so that you can create the perfect gift for your loved one.